Lateral 2D WSe2 p-n Homojunction Formed by Efficient Charge-Carrier-Type Modulation for High-Performance Optoelectronics - Sun, Jiacheng (Advanced materials (Deerfield Beach, Fla.), 2020)
© 2020 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.